(untitled) (Communications in Mathematical Research, 2019)
In this paper we give some characterizations of O-convexity of Banach spaces, and show the criteria for O-convexity in Orlicz-Bochner function space L_M(μ, X) and Orlicz-Bochner sequence space l_M(X_s) endowed with Orlicz norm. Moreover, we give a sufficient condition for the dual of such a space to have the fixed point property.